2022
DOI: 10.5194/acp-22-8639-2022
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of the southern African easterly jet driven by the radiative effect of biomass burning aerosols and its impact on transport during AEROCLO-sA

Abstract: Abstract. The direct and semi-direct radiative effects of biomass burning aerosols (BBAs) are investigated over southern Africa and the southeastern Atlantic during the Aerosols, Radiation and Clouds in southern Africa (AEROCLO-sA) field campaign in September 2017. A reference convection-permitting simulation has been performed using the Meso-NH model with an online dust emission scheme, a strongly absorbing BBA tracer emitted using the daily Global Fire Emissions Database and online-computed backward Lagrangi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…The southern branch of the African Easterly Jet (AEJ‐S) strengthens (i.e., increase in mid‐level (600 hPa) wind speed) in July and achieves a maximum in October (Adebiyi & Zuidema, 2016). This is a large contributing factor to the long‐range, westward transport of central African biomass burning smoke plumes over the remote South Atlantic Ocean (Adebiyi & Zuidema, 2016; Chaboureau et al., 2022; Kuete et al., 2020; Ryoo et al., 2021). Note that non‐refractory aerosols (e.g., sea salt) can also contribute to the total aerosol profile, especially during clean episodes (Zuidema et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The southern branch of the African Easterly Jet (AEJ‐S) strengthens (i.e., increase in mid‐level (600 hPa) wind speed) in July and achieves a maximum in October (Adebiyi & Zuidema, 2016). This is a large contributing factor to the long‐range, westward transport of central African biomass burning smoke plumes over the remote South Atlantic Ocean (Adebiyi & Zuidema, 2016; Chaboureau et al., 2022; Kuete et al., 2020; Ryoo et al., 2021). Note that non‐refractory aerosols (e.g., sea salt) can also contribute to the total aerosol profile, especially during clean episodes (Zuidema et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The 600 hPa wind product from the National Centers for Environmental Prediction (Kalnay et al., 1996) is used as a proxy for the magnitude and direction of the mid‐troposphere smoke aerosol transport to the AMF‐ASI site (Chaboureau et al., 2022; Hsieh & Cook, 2007; Kuete et al., 2020; Ryoo et al., 2022). The NASA Modern Era Retrospective Analysis for Research and Applications Reanalysis version 2 (MERRA‐2) platform incorporates a sophisticated data assimilation system from the Goddard Earth Observing System version 5 (GEOS‐5) model (Buchard et al., 2017; Gelaro et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These layers are lifted and transported to the southeastern Atlantic (SEA) region and S. S. Lee et al: Impacts of an aerosol layer on a midlatitude continental system of cumulus clouds located above or around the top of a large layer or deck of warm cumulus and stratocumulus clouds (Roberts et al, 2005;van der Werf et al, 2010;Che et al, 2022). Note that aerosols in the transported aerosol layers contain organic and black carbon, and these aerosols act as radiation absorbers as well as CCN (Wilcox, 2010;Deaconu et al, 2019;Chaboureau et al, 2022). Reflecting this interest, to better understand roles of aerosol layers above or around cloud tops in cloud development, there have been international field campaigns in the SEA such as the National Aeronautics and Space Administration ObseRvations of Aerosols above CLouds and their intEractionS (ORACLES; https:// espo.nasa.gov/oracles/content/ORACLES, last access: 5 January 2023), the United Kingdom Clouds and Aerosol Radiative Impacts and Forcing (CLARIFY; Redemann et al, 2021), and the French Aerosol, Radiation and Clouds in southern Africa (AEROCLO-sA; Formenti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, biomass burning (BB) aerosol advected from continental Africa, where one-third of the global BB emissions are produced from July to October (Roberts et al, 2009;van der Werf et al, 2010), plays a unique role in modulating the cloud properties due to its short-wave absorption ability as well as its ability to act as CCN. Previous studies have suggested that, as BB aerosols are mainly located above and near the inversion layer, the main role of their radiative effect in the SEA is to strengthen the capping inversion and reduce dry-air entrainment from cloud tops, thereby increasing the LWP and low-level cloud fraction, resulting in a significant impact on the radiation balance (Wilcox, 2010;Gordon et al, 2018;Deaconu et al, 2019;Mallet et al, 2020;Herbert et al, 2020;Chaboureau et al, 2022). When BB aerosols are located in the marine boundary layer, their radiative effect can enhance the decoupled boundary layer and result in a reduction in cloud cover and the LWP, shifting the stratocumulus-to-cumulus transition to the upwind area (Zhang and Zuidema, 2019;Ajoku et al, 2021).…”
Section: Introductionmentioning
confidence: 99%